Parental Alienation: a different field of responsibility for psychologists - Casarini, Karin Aparecida (2023)
The present study aimed to elucidate, through an integrative review of the scientific literature, the ways in which Psychology professionals have understood and acted in situations of Parental Alienation in the national context. The literature review was conducted with the objective of answering the guiding question formulated from the PICO strategy (P: population/patients; I: intervention; C: comparison/control; O: outcome): how have Psychology professionals understood and acted in situations of Parental Alienation in the national context? The bibliographic search was carried out in three databases of scientific productions: Electronic Journals in Psychology (PePSIC); Scientific Electronic Library Online (SciELO); Latin American and Caribbean Literature in Health Sciences (LILACS). And the results allowed us to describe the role of psychologists in the judicial contexts of Parental Alienation, elucidating their potential, contributions and limitations. Noting a specific performance, which combines elements of clinical and legal psychology, establishing a differentiated field of responsibilities of the psychologist.